2005
DOI: 10.1007/s11046-005-1154-3
|View full text |Cite
|
Sign up to set email alerts
|

The mycological and molecular study of Hortaea werneckii isolated from blood and splenic abscess

Abstract: Hortaea werneckii is an environmental dematiaceous fungus found in the halophilic environment. It causes tinea nigra. We report the isolation of H. werneckii from blood and splenic abscess of two patients with acute myelomonocytic leukaemia. H. werneckii grew at room temperature but not at 37 degrees C, it was identified by biochemical tests, growth characteristics and the presence of conspicuous collarette intercalary on dividing yeast cells. The use of specific oligonucleotide primer Hor-F (5'-TGGACACCTTCA T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 6 publications
3
18
0
Order By: Relevance
“…The isolates were sensitive to itraconazole [12,14], ketoconazole [12,45] and voriconazole [12], as we found for our isolates. Gupta et al [14] found resistance to fluconazole, and Ng et al [12] reported that two isolates from patients with acute myeloid leukemia were sensitive to fluconazole and resistant to amphotericin B. In our study, the isolates were resistant to fluconazole and presented low sensitivity to amphotericin B, showing that resistance to these antifungal agents can be found in environmental isolates of H. werneckii; therefore, clinical administration of these agents should be viewed with care.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The isolates were sensitive to itraconazole [12,14], ketoconazole [12,45] and voriconazole [12], as we found for our isolates. Gupta et al [14] found resistance to fluconazole, and Ng et al [12] reported that two isolates from patients with acute myeloid leukemia were sensitive to fluconazole and resistant to amphotericin B. In our study, the isolates were resistant to fluconazole and presented low sensitivity to amphotericin B, showing that resistance to these antifungal agents can be found in environmental isolates of H. werneckii; therefore, clinical administration of these agents should be viewed with care.…”
Section: Discussionsupporting
confidence: 86%
“…There are no such reports for environmental isolates of this fungus; however, studies concerning the in vitro antifungal activity of clinical isolates were found [12,14,45]. The isolates were sensitive to itraconazole [12,14], ketoconazole [12,45] and voriconazole [12], as we found for our isolates. Gupta et al [14] found resistance to fluconazole, and Ng et al [12] reported that two isolates from patients with acute myeloid leukemia were sensitive to fluconazole and resistant to amphotericin B.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations